Induced and thymus‐derived Foxp3+ regulatory T cells share a common niche. Issue 2 (30th October 2013) - Huang, Yi‐Ju; Haist, Verena; Baumgärtner, Wolfgang; Föhse, Lisa; Prinz, Immo; Suerbaum, Sebastian; Floess, Stefan; Huehn, Jochen
<x xml:space="preserve">Abstract</x> Foxp3+ regulatory T (Treg) cells, which play a central role for the maintenance of immune homeostasis and self‐tolerance, are known to be both generated in the thymus (thymus‐derived, tTreg cells) and in the periphery, where they are converted from conventional CD4+ T cells (induced Treg (iTreg) cells). Recent data suggest a division of labor between these two Treg‐cell subsets since their combined action was shown to be essential for protection in inflammatory disease models. Here, using the transfer colitis model, we examined whether tTreg cells and iTreg cells fill different niches within the CD4+ T‐cell compartment. When naive T cells were co‐transferred with either pure tTreg cells or with a mixture of tTreg cells and iTreg cells, induction of Foxp3+ Treg cells from naive T cells was not hampered by preoccupation of the Treg‐cell niche. Using neuropilin‐1 (Nrp1) as a surface marker to separate tTreg cells and iTreg cells, we demonstrate that tTreg cells and iTreg cells alone can completely fill the Treg‐cell niche and display comparable TCR repertoires. However, when transferred together Nrp1+ tTreg cells outcompeted Nrp1− iTreg cells and dominated the Treg‐cell compartment. Taken together, our data suggest that tTreg cells and iTreg cells share a common peripheral niche.